Insight on Environmental Genomics. - Faure, Denis (Elsevier Science, 2016)
Bringing together the latest methodological and scientific progress in the various research areas in the field of Environmental Genomics, this book discusses the characterization of the structure and dynamics of life, the study of the evolution and adaptation of genes and genomes, the analysis of degraded and/or old DNA, and the functional and genomic ecology of populations and communities.iA It also considers access to the production and sharing of NGS data and the quality of this data. As the product of the collective discussion of the active French scientific community, the book presents not only the latest technologies in the development of new sequencing methods, but also the resulting issues, challenges and prospects, in order to identify those aspects with the greatest potential for modeling and exploring the function of ecosystems.